2005
DOI: 10.1097/01.sla.0000186173.14696.ea
|View full text |Cite
|
Sign up to set email alerts
|

Crohn??s Disease Patients Carrying Nod2/CARD15 Gene Variants Have an Increased and Early Need for First Surgery due to Stricturing Disease and Higher Rate of Surgical Recurrence

Abstract: Nod2/CARD15 variants are associated with early initial surgery due to stenosis and with surgical recurrence in Crohn's disease. Patients with these variants could benefit from preventive and/or early therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 44 publications
5
103
1
7
Order By: Relevance
“…It is also possible that different defensins may be specific to CD and UC variations [17] . These observations demonstrate the fine-tuning of [18] . Despite the well-demonstrated and replicated role of CARD15 mutations in the susceptibility for CD in the majority of Caucasian populations [19][20][21][22][23] , no mutations have been found in Asian [24][25][26][27] and in several European populations.…”
Section: Introductionsupporting
confidence: 53%
“…It is also possible that different defensins may be specific to CD and UC variations [17] . These observations demonstrate the fine-tuning of [18] . Despite the well-demonstrated and replicated role of CARD15 mutations in the susceptibility for CD in the majority of Caucasian populations [19][20][21][22][23] , no mutations have been found in Asian [24][25][26][27] and in several European populations.…”
Section: Introductionsupporting
confidence: 53%
“…earlier need for first surgery and reduced postoperative disease-free interval [42][43][44] . Some studies have also tried to identify genetic factors associated with response to treatment.…”
Section: Genetic Predictors Of CD Coursementioning
confidence: 99%
“…Studies of genotype-phenotype relationship suggest that these variants are associated with ileal location and the development of intestinal strictures. In a study evaluating the influence of NOD2/CARD15 variants on CD outcomes including 170 patients (70 of who had been operated on), Alvarez-Lobos and co-workers found that those patients carrying gene variants had a higher risk of surgical POR [21] . Recently, in another Mediterranean area study including a total of 110 patients, although these findings were not completely reproduced, those patients the L1007fs mutation also had higher rates of reoperation [22] .…”
Section: Patient and Disease Characteristicsmentioning
confidence: 99%